Management of Oral Discoid Lupus Erythematosus - Raziv Ganesha (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Background: Systemic diseases have manifestations in the oral cavity with a variety of lesions that have similar types or forms and can be the first manifestations that appear before the manifestations spread to other areas, therefore a thorough initial examination of the oral cavity is very important to determine indications of systemic conditions. Lupus Erythematosus is an autoimmune disease that is associated with hyperactivity of the immune system, in which the immune system which functions as a protector of the body experiences an abnormality that is unable to distinguish between foreign objects /own cells. Oral Discoid Lupus Erythematosus is a manifestation of Systemic Lupus Erythematosus in the oral cavity. Case: a 47-year-old woman came with complaints of canker sores in her mouth. Canker sores have occurred since the previous 7 months, sometimes heal and then reappear repeatedly. The patient said that she started experiencing thrush after giving birth 10 years ago. Case Management: the patient was referred for a complete blood count and ANA test then the patient was given methylprednisolone 4 mg at a dose of 3x1 a day, topical anti-inflammatory drugs, and B-complex vitamins. Discussion: Oral Discoid Lupus Erythematosus has clinical features of ulcers and erosions surrounded by white striae on the mucosal. Diagnosis confirmed from clinical features and ANA test which showed positive. Conclusions: The treatment was successful because the correct diagnosis with collaboration was made to produce the right treatment plan accompanied by the patient's cooperation in carrying out the treatment